Key Determinants of Cell-Mediated Immune Responses: A Randomized Trial of High Dose Vs. Standard Dose Split-Virus Influenza Vaccine in Older Adults - Verschoor, Chris P.; Haynes, Laura; Pawelec, Graham; Loeb, Mark; Andrew, Melissa K.; Kuchel, George A.; McElhaney, Janet E. (Frontiers in Aging, 2021)
Background. Efforts to improve influenza vaccine effectiveness in older adults have resulted in some successes, such as the introduction of high-dose split-virus influenza vaccine (HD-SVV), yet studies of cell-mediated immune responses to these vaccines remain limited. We have shown that the activity of the cytolytic mediator, granzyme B (GrB), in peripheral blood mononuclear cells (PBMC) challenged with influenza A/H3N2 virus, correlates with protection against influenza following standard dose vaccination (SD-SVV) in older adults. Further, the interferon-gamma (IFNg)) to interleukin-10 (IL-10) ratio correlates with protection depending on the timing of vaccination relative to exposure to influenza. Methods. In a double-blind trial (ClinicalTrials.gov NCT02297542) older adults (≥65 years, n=582) were randomized to receive SD-SVV or HD-SVV (Fluzone®) from 2014/15 to 2017/18. Young adults (20-40 years, n=79) received SD-SVV. At 0, 4, 10 and 20 weeks post-vaccination, serum antibody titers, IFNg, IL-10, and inducible granzyme B (iGrB) were measured in ex vivo influenza virus-challenged PBMC. iGrB is defined as the fold change in GrB activity from baseline levels (bGrB) in circulating T cells. Responses of older adults were compared to younger controls, while specifically for older adults we analyzed effects of age, sex, cytomegalovirus (CMV) serostatus, frailty, and vaccine dose. Results. Prior to vaccination, younger adults produced significantly higher IFNγ, IL-10 and iGrB levels, but with no difference in the IFNg:IL-10 ratio. Relative to SD-SVV recipients, older HD-SVV recipients exhibited significantly lower IFNg:IL-10 ratios at 4 weeks post-vaccination. In contrast, IFNg and iGrB levels were higher in younger SD vs. older SD or HD recipients; only the HD group showed a significant IFNγ response to vaccination compared to the SD groups while all three groups showed a significant iGrB response to vaccination. In a regression analysis, frailty was associated with lower IFNγ levels, whereas female sex and HD-SVV with higher IL-10 levels, while age and SD-SVV were associated with lower iGrB levels.